2005
DOI: 10.1158/1541-7786.mcr-05-0074
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Low-Dose Radiation Exposure Leads to Accumulation of DNA Damage and Profound Alterations in DNA and Histone Methylation in the Murine Thymus

Abstract: Thymus, an important component of hematopoietic tissue, is a well-documented ''target'' of radiation carcinogenesis. Both acute and fractionated irradiation result in a high risk of leukemia and thymic lymphoma. However, the exact mechanisms underlying radiation-induced predisposition to leukemia and lymphoma are still unknown, and the contributions of genetic and epigenetic mechanisms in particular have yet to be defined. Global DNA hypomethylation is a well-known characteristic of cancer cells. Recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 51 publications
4
99
0
1
Order By: Relevance
“…The DNA hypomethylation observed after irradiation was related to DNA repair . It also correlated with the radiationinduced alterations in the expression of DNA methyltransferases, especially de novo methyltransferases DNMT3a and DNMT3b Pogribny et al, 2005]. Most importantly, the radiation-induced global genome DNA hypomethylation appeared to be linked to genome instability in the exposed tissue Raiche et al, 2004;Loree et al, 2006].…”
Section: Epigenetic Changes In the Directly Exposed Tissuementioning
confidence: 90%
“…The DNA hypomethylation observed after irradiation was related to DNA repair . It also correlated with the radiationinduced alterations in the expression of DNA methyltransferases, especially de novo methyltransferases DNMT3a and DNMT3b Pogribny et al, 2005]. Most importantly, the radiation-induced global genome DNA hypomethylation appeared to be linked to genome instability in the exposed tissue Raiche et al, 2004;Loree et al, 2006].…”
Section: Epigenetic Changes In the Directly Exposed Tissuementioning
confidence: 90%
“…18 Endogenous factors acting through three secondary pathways related to decreased DNA methyltransferase expression, 19,20 non-coding RNA silencing 21,22 and defective DNA repair, 23,24 may also have a direct causal role in global DNA hypomethylation. Factors that activate these three endogenous pathways may lead directly to a loss of global DNA methylation, may also cause chromatin modifications leading to hypomethylation, or may only be an intermediate step leading to histones modifications that are linked to global DNA hypomethylation.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…For example, observed epigenetic changes were mostly in DNA hypermethylation at repetitive elements SAT2 and MLT1A in progeny of irradiated HPV-G cells after 20 passages, but hypomethylation, which is not identified with respect to the sequence context, was also detected [6]. Reduction of various epigenetic indicators (the levels of global genomic hypomethylation, trimethylation of histone H4-Lys20, methyltransferases Dnmt1 and Dnmt3a/b, methyl-binding proteins MeCP2 and MBD2) has been observed in experiments using rodents exposed to acute (2.5 Gy) or chronic (0.5 Gy) irradiation [7,8]. Hypermethylation of the p16 tumorsupressor gene in mouse exposed to chronic low-dose radiation (X-ray, 0.5 Gy, 10 days) was revealed.…”
Section: Discussionmentioning
confidence: 94%
“…For example, it was revealed that there are numerous epigenetic differences in MZ twins and that such epigenetic variation can serve as a new source of putative molecular substrates for discordance of MZ twins [19]. A number of environmental factors, both chemical and radiation have been found to alter the epigenome, including DNA methylation [5][6][7][8][9][10]. It should be emphasized that most of the investigations devoted to evaluation of the epigenetic effects of radiation (X -rays and γ -rays, range of doses of 0.1 to 2.5 Gy) was performed using cell cloning techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation